Genetic x environment interaction on agronomic characters and yield components of sweet sorghum (Sorghum bicolor) mutant strain - Endang Endang; ISWARI SARASWATI DEWI; AMIN NUR; ROSSA YUNITA; MASTUR (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Lestari EG, Dewi IS, Nur A, Yunita R, Mastur. 2019. Genetic x environment interaction on agronomic characters and yield components of sweet sorghum (Sorghum bicolor) mutant strain. Biodiversitas 20: 3705-3714. Sweet sorghum (Sorghum bicolor (L.) Moench) belongs to cereal plants that have prospects for commercial development in Indonesia, since it can adapt widely in sub-optimal land, and has many functions. However, there is still limited sweet sorghum variety that has been released in Indonesia. The study aimed to evaluate the influence of genetic x environment interaction on agronomic characters and yield components of sweet sorghum mutant strain. Adaptation test was held in 8 locations in Indonesia, namely Pekalongan, Bantul, Gunung Kidul, Lampung, Malang, East Lombok, Bontobili and Maros, from May to November 2017. The material tested was 10 M7 mutant strains and two check varieties (Numbu and Super 1). The experiment was arranged in a randomized complete block design (RCBD). There were three replications in form of blocks and each block consisted of 40 sorghum plants. The result showed that genetic x environment interaction affected the agronomic characters and yield components of sweet sorghum. Several characters such as plant height, panicle diameter, seed production, sugar brix and stem juice volume of sweet sorghum mutants were greater than check varieties. The highest seed yield was found in MB-1 strain of sweet sorghum mutant that cultivated in Pekalongan site.